Inhibition of eukaryotic elongation factor-2 confers to tumor suppression by a herbal formulation Huanglian-Jiedu decoction in human hepatocellular carcinoma. (22nd April 2015) - Wang, Ning; Feng, Yibin; Tan, Hor-Yue; Cheung, Fan; Hong, Ming; Lao, Lixing; Nagamatsu, Tadashi
Abstract: Ethnopharmacological Relevance: An oriental medicinal formulation, Huanglian Jiedu Decoction (HLJDD), has been well documented in few Traditional Chinese Medicine Classics 1300 years ago for treatment of heat and dampness-related diseases. Its effect is well accepted in Asian community, including China, Japan and Korea. Recent studies have postulated HLJDD as a regimen for cancer treatment, especially liver cancer, but the underlying mechanism is unknown. The aim of this study was to examine the suppressive effect of HLJDD on the growth of hepatocellular carcinoma (HCC) and its possible underlying mechanism. Methods: Chemical composition of HLJDD was analyzed by high performance liquid chromatography. The tumor suppressive effect of HLJDD was determined on both HCC cells and xenograft model. Nascent protein synthesis was detected with Click-IT protein labeling technology; protein expression was determined by immunoblotting and imunnohistochemical analysis. Results: Quality analysis revealed that HLJDD of different batches is consistent in both chemical composition and bioactivities. HLJDD inhibited HCC cell proliferation at its non-toxic doses, and suppressed growth and angiogenesis in xenografted murine model. HLJDD suppressed the synthesis of nascent protein via inactivation of eEF2 without deregulating the translation initiation factors. The major components in HLJDD, geniposide, berberine and baicalin, additively act on eEF2, and contributed to the responsible activity. HLJDD-activated eEF2 kinase (eEF2K) led to eEF2 inactivation, and activation of AMPK signaling may be responsible for the eEF2K induction. Blocked AMPK activity in HLJDD-treated HCC cells attenuated eEF2K activation as well as the inhibitory effect of the formula. In nutrient deprived HCC cells with inactivated eEF2, the inhibitory effect of HLJDD in tumor cell expansion was interfered. Conclusion: Our results indicate that HLJDD has potential in blocking HCC progression with involvement of eEF2 inhibition. Graphical abstract: